The Effect of Hopping Exercises on the Feedforward and Feedback Activity and Start Time of Selected Lower Limb Muscles in Athletes with Functional Ankle Instability in Single Leg Jump Task - Sasan Arjang; Farideh Babakhani; Ramin Balouchi (Vesnu Publications, 2020)
Introduction: The aim of this study was to investigate the effect of hopping exercises on the feedback and feedforward activity of selected lower limb muscles in single leg jump landing task in athletes with functional ankle instability.Materials and Methods: 24 male athletes (12 in the control group and 12 in the training group) with functional ankle instability participated in this randomized clinical trial. Hopping exercises were given for six weeks, three times a week to the experimental group. The control group continued their routine exercise three sessions per week. The electric activity of Peroneus Longus, Tibialis Anterior, Medial Gastrocnemius, gluteus medius, and gluteus maximus muscles in the jump landing, before and after the hopping exercises were collected.Results: The results of this study showed that after six weeks of hopping exercises, there was a significant effect on the onset of activity of the Peroneus Longus and gluteus medius muscles (P ≤ 0.001). There was a significant increase in the activity of Peroneus Longus (P ≤ 0.003), Medial Gastrocnemius (P ≤ 0.005), and gluteus medius (P ≤ 0.001) muscles in 100 milliseconds before the first contact of the foot on the ground. In addition, Peroneus Longus (P ≤ 0.001) and gluteus medius (P ≤ 0.001) activity increased significantly between 100-200 milliseconds after the first contact of the foot on the ground. However, no significant difference was observed in muscle activity of the untreated control group (P > 0.050). No significant change was recorded in the activity of the Tibialis Anterior, Medial Gastrocnemius, and gluteus maximus muscles (P > 0. 050).Conclusion: Six weeks of hopping exercises seem to reduce the time interval before the onset of activity and increase the activity amplitude for aforementioned muscles in single leg jump landing in athletes with functional ankle sprain. Therefore, while planning therapeutic exercise programs for athletes with functional ankle instability, it may be beneficial to have a look at hoping exercises.